Etnobiologi Kota Amlapura, Karangasem, Bali: Amla, Amlapura dan Phyllanthus emblica L. (Phyllanthaceae) - Ary Prihardhyanto Keim; Tukul Rameyo Adi; Muhamad Nikmatullah; Nissa Arifa; Fauzi Akbar; Wawan Sujarwo (The Ethnobiological Society of Indonesia, 2020)
Amlapura is a Sanskrit name for the city of Karangasem and the result of the ethnobiological research conducted in this study indicates that it refers to a species of plant named Phyllanthus emblica (Phyllantaceae). In Indonesian, particularly Javanese the name is known as ‘malaka’, ‘mlaka’, ‘kemloko’, or ‘mloko’. This present ethnobiological study also raises a possibility that the name ‘mlaka’ is an indigenous Austronesian word instead and entered Sanskrit through Dravidian languages.